Institutional Ownership, Board Size, Growth Opportunities, Net Working Capital and Cash Holding - Christy Valent; Yanti Yanti (International Journal of Application on Economics and Business, 2023)
This study aims to investigate empirically the effect of institutional ownership, board size, growth opportunities, and net working capital toward cash holding, utilizing firm size and cash flow ratio as control variables on manufacture industry listed on the Indonesia Stock Exchange during 2016 to 2019 period. This study’s valid data consisted of 51 companies and the sample was chosen using purposive sampling approach. The data in this study is processed with Eviews 12 and Microsoft Excel 2016. According to the findings, board size and net working capital have a significant positive effect on cash holding, institutional ownership has insignificant positive effect on cash holding and growth opportunities has insignificant negative effect on cash holding.